Desain Video Ajar Blended Learning Mata Kuliah Pencak Silat - Sasmitha, Weny; Amra, Frizki; Candra, Juli; Zulbahri, Zulbahri (Ilmu Olahraga, 2022)
Pencak silat course is one of the Important practical courses at Universitas Negeri Padang. The unavailability of teaching media that is in accordance with the model and learning method used is the main problem that will be solved in this study. The purpose of this study is to produce teaching media (videos) that are in accordance with the learning model used today (blended learning) and can be used in the process of learning activities. The stages/methods of implementing this research use the ADDIE model development method which has 5 phases of interrelated activities. The research was carried out in the Physical Education, Healt and Recreation Departemen Universitas Negeri Padang with 200 students as respondent and 5 user lecturers. Data collection techniques were carried out by observation, interviews and using a questionnaire. Data were analyzed descriptively qualitatively and quantitatively. The results of the study are 7 audio-visual media (video) each 5 minutes in duration that has met the Valid and Practical categories for use in pencak silat courses at the Sports Science faculty of Universitas Negeri Padang